y2-11y-12=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -12 and whose sum is -11.

-12,1

Write the factored form using these integers.

(y-12)(y+1)=0

(y-12)(y+1)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

y-12=0

y+1=0

Set the first factor equal to 0.

y-12=0

Add 12 to both sides of the equation.

y=12

y=12

Set the next factor equal to 0.

y+1=0

Subtract 1 from both sides of the equation.

y=-1

y=-1

The final solution is all the values that make (y-12)(y+1)=0 true.

y=12,-1

Solve for y y^2-11y-12=0